Parameter Estimation of Metal Plasticity from Time History Data of Taylor Impact Test. (2017) - Sen, Subhajit; Banerjee, Biswanath; Shaw, Amit
Abstract: Characterisation of material response under intensive dynamic loading due to explosion or projectile impact bears great importance as material properties are significantly influenced by strain rate. Among the several available methods, Taylor impact test is the simplest experimental approach for characterizing plastic behaviour of metals under high strain rate (up to 10 5 s -1 ). Here in, a cylindrical rod is impacted upon a rigid stationary anvil and the dynamic yield strength is estimated from the final deformed dimensions of the rod. Development of high speed photography enables the capturing of the time evolution of these dimensions experimentally. These time histories are rich with information about the material plastic behaviour and thus using them in estimating metal plasticity would be an important development. In the present study, an attempt is made to formulate an inverse problem and estimate parameters of metal plasticity using the time history data obtained from the Taylor impact test.